The study on implementation of lean production system in front disc D54T line at Sapura Machining Corporation Sdn - Najibah, Anuar (2012)
This final year project is about Lean Production System (LPS) implementation that has been applied at Sapura Machining Corporation Sdn Bhd.This study is deals with the development of a new approach for supporting the improvement, focusing on Front Disc D54T line in order to achieve excellent performances that can increase the productivity,quality of product and benefits in future. In reality, productivity improvement is a concern of industry. This research is an alternative to reduce idle efficiency of production.By studying the line balancing method can lead to improvement.Besides that,there are still have problems in the entire industry due to variable process time,line balancing problems deals with multiple workstations, human factors,and length of cycle time.Therefore,analyzing and studying this current problem is important through the methodology of the four phases which are descriptive, examination,implementation, and monitoring phase. This study is done by experimentally. Lean techniques are applied and practiced such as by doing time measurement, cycle time, standardized work,establishing Takt time,eliminate waste (MUDA) and do continuous improvement (Kaizen).By this,it can enhance the learning and understanding of basic concepts of lean and create ability to implement Lean Production System (LPS) in current manufacturing industry to achieve required standard and goal.